Live and wet markets: Food access versus the risk of disease emergence - Naguib, M.M.; Ruiyun Li; Jiaxin Ling; Grace, Delia; Hung Nguyen-Viet; Lindahl, Johanna F. (Elsevier, 2021)
Emerging zoonotic diseases exert a significant burden on human health and have considerable socioeconomic impact worldwide. In Asia, live animals as well as animal products are commonly sold in informal markets. The interaction of humans, live domestic animals for sale, food products, and wild and scavenging animals, creates a risk for emerging infectious diseases. Such markets have been in the spotlight as sources of zoonotic viruses, for example, avian influenza viruses and coronaviruses, Here, we bring data together on the global impact of live and wet markets on the emergence of zoonotic diseases. We discuss how benefits can be maximized and risks minimized and conclude that current regulations should be implemented or revised, to mitigate the risk of new diseases emerging in the future.